The potential productivity of spruce to rise of mass of tree trunk in a changing climate - Matsiusheuskaya, Katsiaryna V.; Kisialiou, Victar N.; Jarotau, Alaksey E.; Mitrachovich, Petr A. (Journal of the Belarusian State University. Geography and Geology, 2017)
The results of the study of the dynamics of radial growth of spruce in the zonal edaphic and climatic conditions of Belarus. It was found that spruce realize its potential productivity in the growth of the individual maximum radial growth is not dependent on climate variability, as in cold weather, and when warming, excluding weather extremes, in the age of asynchrony year-dinamics. This ensures its stability in unstable environments with optimal use of resources growing environment.